2021
DOI: 10.1097/jtn.0000000000000571
|View full text |Cite
|
Sign up to set email alerts
|

Mass Casualty Mini Drills on Trauma Surgery Department Staff Knowledge: An Educational Improvement Study

Abstract: Background: Over the last decade, the United States has witnessed an increase in mass casualty incidents (MCIs). The outcome of an MCI depends upon hospital preparedness, yet many hospitals are unfamiliar with their facility MCI procedure. Educational training drills may be one method to improve staff knowledge of policy and procedure. Objective: This study aimed to improve knowledge gained through educational MCI mini drills of institutional mass casua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…51,52 Repeated paper-based mini-drills have been shown to increase participant knowledge of institutional disaster policy and procedures, potentially improving preparedness for MCIs. 53 Nevertheless, tabletop simulations cannot fully replace real-world multicentre, multi-organisational drills. 48,54 Large-scale drills commonly include multiple trauma centres, regional hospitals, law enforcement, defence force, and emergency services, and provide a unique opportunity to stress and evaluate existing protocols.…”
Section: Education Training and Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…51,52 Repeated paper-based mini-drills have been shown to increase participant knowledge of institutional disaster policy and procedures, potentially improving preparedness for MCIs. 53 Nevertheless, tabletop simulations cannot fully replace real-world multicentre, multi-organisational drills. 48,54 Large-scale drills commonly include multiple trauma centres, regional hospitals, law enforcement, defence force, and emergency services, and provide a unique opportunity to stress and evaluate existing protocols.…”
Section: Education Training and Simulationmentioning
confidence: 99%
“…Conversely, 58% of trauma centres in Australia, Canada, England, and NZ had activated their disaster plan (32% in the past 2 yr); 79% reported conducting a practice drill for an MCI and 48% had completed a multi-agency real-world exercise in the past 2 yr. 13 Regardless of methodological choice, recommendations outlined as a result of training exercises should be acted upon in a timely way and then tested to ensure that improvements have been effective. 18,53 Skryabina and colleagues 57 found that deficiencies in emergency plans, procedures, resources, and communications identified through simulation exercises were often not integrated into an updated emergency plan. Gabbe and colleagues 13 reported that most (50/52) centres in Australia, Canada, England, and NZ that had undertaken a practice drill had reported the findings, and 80% of the time, the findings were incorporated in the revised disaster plan.…”
Section: Education Training and Simulationmentioning
confidence: 99%